DOMINION THEOLOGY PRESENT IN PRISON SCHOOL. - de Sena, Daniel (2025)
Democracy is constantly under attack by those interested in stealing it to exercise authoritarianism. Furthermore, we have before us other ways of subjecting it to unfavorable conditions in order to serve private ends. This work seeks to understand worldviews that place democratic secularism under attack, even unintentionally, as is the case with the intersubjective relationships of everyday life in the classroom and here, in a prison environment. This is a bibliographic review study, with a cross-section of labor practices in a prison environment, regarding themes such as democracy, secularism, and the public sphere, thus in tune with reflections despite autobiographical experience. As a result of the research, it was possible to demonstrate, even as a provocation for new analyses, that there is a strong presence of some religions in prison environments to the detriment of other forms of religious manifestations, mainly minority ones, which is, in itself, a form of affront to the secularism of the State and, consequently, to democracy.